Emerging trends and new developments in monoclonal antibodies: A scientometric analysis (1980–2016) - Lai, Yunfeng (Hum Vaccin Immunother, 2017)
This article aims to explore the intellectual landscape of the study of monoclonal antibody (mAb), mainly to identify thematic trends, landmark articles and emerging trends involving mAb. This work is based on 4 sets of bibliographic records retrieved from the Web of Science. The final data set, consisting of 7,385 bibliographic records, was combined from the 4 individual data sets. This study explores the document co-citation clusters of 7,385 bibliographic records to identify the origin of mAb and the hot research specialty of this domain by applying CiteSpace software. We examined the mAb evolution from 4 perspectives: (1) Clusters of cited references regarding mAb; (2) Cited authors as contributors to mAb research; (3) Institutions participating in mAb research; and (4) Cited journals regarding mAb. The technical development, drug development and clinical applications of mAbs were analyzed. Through data analysis, we have identified the new directions for the exploration of mAbs, interactions between mAb technologies and diseases, and evolving global collaboration among institutions.